Menumbuhkembangkan Karakter Anak Panti Melalui Permainan Edukatif Studi Panti Asuhan Ulul Azmi Kota Cimahi - Eneng Martini; Jajang Hendar H; Lili Halimah; Purwanto Purwanto (Jurnal Pengabdian Masyarakat Waradin, 2024)
Character is very important to instill from an early age, because nowadays quite a few children grow up with global flows and intense use of gadgets. The implication of this is their character development in the future. In this program, the service activities we hold are given the theme "Growing the Character of Orphanage Children Through Educational Games", with a case study at the Ulul Azmi Orphanage, Cimahi City. This program aims to provide alternative positive activities for children so they can be free from using gadgets and at the same time refresh their minds. Character development in this activity is carried out through two main stages. First, this program targets elementary school children from grade one to grade six, with a more interactive method so that it is not boring. Second, through the medium of educational games, various moral messages can be conveyed in a way that is more interesting and easy for children of their age to understand. Thus, it is hoped that this program can help orphanage children to form positive characters from an early age.